1991
DOI: 10.1113/jphysiol.1991.sp018537
|View full text |Cite
|
Sign up to set email alerts
|

Afferent pathway(s) for pharyngeal dilator reflex to negative pressure in man: a study using upper airway anaesthesia.

Abstract: SUMMARY1. To determine the afferent pathways mediating pharyngeal dilator muscle activation in response to negative airway pressure in man, we recorded genioglossus electromyogram (EMG) activity (via intra-oral bipolar surface electrodes) in response to 500 ms duration pressure stimuli of -15 and -25 cmH20 in normal, conscious, supine subjects relaxed at end-expiration; responses were compared before and after upper airway anaesthesia.2. Six rectified and integrated EMG responses were bin averaged for pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 13 publications
8
142
3
Order By: Relevance
“…27,28 The afferent peripheral nerves in the airway mucosa respond to stimulation by fumes by secreting tachykinin, CGRP, and SP, which are required for neuroendocrinological inflammation. [29][30][31] We found that CGRP-positive staining was substantially more prevalent in the uvular mucosa of smokers compared to PGP 9.5 and SP staining. In particular, CGRP staining was increased in the uvular mucosa of patients exposed to smoking for > 10 PY.…”
Section: Discussionmentioning
confidence: 64%
“…27,28 The afferent peripheral nerves in the airway mucosa respond to stimulation by fumes by secreting tachykinin, CGRP, and SP, which are required for neuroendocrinological inflammation. [29][30][31] We found that CGRP-positive staining was substantially more prevalent in the uvular mucosa of smokers compared to PGP 9.5 and SP staining. In particular, CGRP staining was increased in the uvular mucosa of patients exposed to smoking for > 10 PY.…”
Section: Discussionmentioning
confidence: 64%
“…Evidence suggests that these reflex mechanisms are pressure sensitive [112,[144][145][146], and interference with them could lead to an imbalance between intrapharyngeal pressure and the contraction of upper airway dilating muscles, resulting in obstructive apnoeas [3]. The importance of such protective reflexes is supported by the finding of fatal pharyngeal airway closure in rabbits, in which upper airway reflexes are abolished by topical anaesthesia [150].…”
Section: Upper Airway Reflexesmentioning
confidence: 68%
“…Contributions from both supraglottic and subglottic receptors appear to be involved, and topical anaesthesia blocks the response when the glottis is closed [112]. This response is reduced during NREM sleep [154].…”
Section: Responses To Negative Pressurementioning
confidence: 95%
See 2 more Smart Citations